Losing control? Unions' representativeness, "pirate" collective agreements and wages - Claudio Lucifora; Daria Vigani (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
This paper documents the evolution of sector-level collective agreements in Italy and estimates the wage effects of the diffusion of non-representative agreements, often signed by unknown organisations i.e. pirate agreements. Using employer-employee data from Social Security Archives, we find evidence of a signicant dumping effect on wages associated with different types of non-representative agreements (-15% with respect to regular collective agreements). We show that half of the wage differential associated with pirate agreements is due to selection effects. Also, heterogeneous effects are found across firm size and industry affiliation. Finally, we show that firms with non-representative agreements are also less likely to comply with negotiated minimum wages set in representative collective agreements.
Keywords: J52; J31; J41; 330; collective bargaining; collective agreements; representativeness; wage differentials; Tarifvertrag; Branche; Lohn; Niedriglohn; Italien